Hematologic Profiles of Ethiopian Preterm Infants With Clinical Diagnoses of Early-Onset Sepsis, Perinatal Asphyxia, and Respiratory Distress Syndrome - Zemene Tigabu Kebede MD; Yohannes Hailu Matebe MD; Abayneh Girma Demisse MD; Mulugeta Ayalew Yimer MD; Amha Mekasha MD; Alemayehu Worku MD; Asrat Demtse Gebremedhin MD; Elizabeth M. McClure MD; Assaye K. Nigussie MD; Bogale Worku MD; Netsanet Workneh Gidi MD; Gesit Metaferia MD; et al. (SAGE Publishing, 2020)
Objective. To determine the hematologic profile of preterm infants with regard to different diseases. Methods. A prospective, cross-sectional, observational study, conducted in 5 hospitals in Ethiopia from July 2016 to May 2018. Preterm babies <7 days of age were included and investigated with complete blood counts (CBC) and other investigations, accordingly. Results. Out of 4919 preterms, 3852 (78.3%) were admitted to a newborn intensive care unit, and of these, 68.3% had a CBC performed. The mean values of hemoglobin, white blood cell (WBC) and platelet counts were 17.9 mg/dL; 12 685 cells/mm 3 , and 159 340 cells/mm 3 , respectively. Early onset neonatal sepsis (EONS) 1433 (37%), asphyxia 266 (6.9%), and respiratory distress syndrome (RDS) 1738 (45.3%) were common reasons for admission. The WBC count was <5000 cells/mm 3 for 8.8%, 9.0%, and 11.1% of neonates with EONS, asphyxia and RDS, respectively. The hemoglobin value was <7 mg/dL for 0.6%, 1.7%, and 0.4% of preterm infants with EONS, asphyxia, and RDS, respectively. The platelet count was <50 000 cells/mm 3 for 16.8%, 17.7%, and 19.8% of preterms admitted with a diagnosis of EONS, asphyxia, and RDS, respectively. Conclusion . WBC and platelet counts were the most common to be associated with EONS, asphyxia, and RDS. Further study is recommended to determine the effect of abnormal hematologic profile on the outcome of preterm babies.